EFEKTIVITAS PROSES DAN SISTEM PENGAJUAN KLAIM JAMINAN HARI TUA (JHT) BAGI PENERIMA UPAH (PU) PADA BPJS KETENAGAKERJAAN CABANG SIKKA MAUMERE - Fransiskus Jetrison Renaldo Dura Fono; Andreas Rengga; Elisabet Luju (Jurnal Projemen UNIPA, 2026)
The Old Age Security (JHT) program is a form of employment social protection that aims to ensure the continuity of workers’ welfare after they are no longer productive. The high volume of JHT claims, particularly for wage earners, requires an effective service process and system. This study aimed to analyze the effectiveness of the process and system for submitting JHT claims for wage earners at BPJS Ketenagakerjaan Sikka Maumere Branch, as well as to identify obstacles and improvement efforts undertaken. The research method used was descriptive qualitative, with data collection techniques through observation, documentation, and interviews during the internship period. The results of the study show that the JHT claim submission process has followed the applicable standard operating procedures (SOP), both through online services (Lapak Asik and the Jamsostek Mobile (JMO) application) and offline services. However, the effectiveness of the system still faces various obstacles, including discrepancies in participant data, limited digital literacy among participants, and technical constraints in the online system. Improvement efforts have been carried out through increased socialization, participant assistance, and optimization of digital systems. This study concludes that the effectiveness of the JHT claim process and system at BPJS Ketenagakerjaan Sikka Maumere Branch is fairly effective, but still requires continuous improvement to enhance service quality and participant satisfaction.